The Analysis of Requirements Developing Teaching Materials in Writing Folklore with Javanesse Language Based on Local Wisdom (Journal of Primary Education, 2017)
This study aims to describe and analyze the requirement developing of teaching materials in writing folklore with javanesse languagebased on local wisdom according to the perception of teachers and students of fourth grade elementary school. The research method used is R & D four-D models by Thiagarajan. The stages of research are define, design, development, and dissemination. The analysis is using qualitative analysis and quantitative analysis. The results showed that teachers and learners need teaching materials that are developed based on aspects of contents or materials, presentation aspects, linguistic aspects, and graphics aspects. (1) The developed teaching material consists of folklore material originating from the local area with the content of local wisdom in the form of Javanese values or ethics, (2) The teaching materials are equipped with the beginning, the contents, and the end with the systematic presentation of the material (3) The language used is a simple and communicative Javanese language; (4) A4-size teaching materials and complited with colored illustrations in accordance with the folklore theme.